Ovarian neoplasm imaging - Acharya, U. Rajendra; Guerriero, Stefano; Suri, Jasjit S. (Springer US Imprint: Springer, 2013)
Luca Saba MD, is a researcher in the field of Multi-Detector-Row Computed Tomography, Magnetic Resonance, Ultrasound, Neuroradiology, and Diagnostic in Vascular Sciences. His works, as lead author, achieved more than 120 high impact factor, peer-reviewed Journals. He is well known speaker and has spoken over 45 times at national and international levels. Dr. Saba has won 12 scientific and extracurricular awards during his career. U Rajendra Acharya, PhD, DEng is is a visiting faculty in biomedical engineering department at the Ngee Ann Polytechnic, Singapore. He is also adjunct professor at the University of Malaya, Malaysia, adjunct faculty at Singapore Institute of Technology - University of Glasgow, Singapore, and associate faculty at Singapore Institute of Management University, Singapore. He has published more than 285 papers, including 178 papers in refereed international SCI-IF (Science Citation Index - Impact Factor) journals, as well as international conference proceedings (48), textbook chapters (62), and books (16). Stefano Guerriero MD, Born Siracusa (Italy) 10 October 1961. Medical doctor University of Pisa 24 October 1988. Postgraduate in Obstetrics and Gynecology University of Pisa october 1992. His works, as lead author, achieved more than 130 high impact factor, peer-reviewed, Journals as British Medical Journal, Americal Journal of Obstetrics and Gynecology, Fertility and Sterility, Human Reproduction, Journal of Ultrasound in medicine, Menopause, Maturitas, Ultrasound Obstetrics and Gynecology. Until now Associate Professor of obstetrics and Gynecology University of Cagliari.. Editor of Ultrasound in Obstetrics and Gynecology from 2011 Jasjit S. Suri, MS, PhD, MBA is an innovator, visionary, scientist, and an internationally known world leader in the field of Healthcare Imaging and biomedical devices. Dr. Suri was the recipient of Director General's Gold medal in 1980 and the Fellow of American Institute of Medical and Biological Engineering (AIMBE), awarded by National Academy of Sciences, Washington DC in 2004. Dr. Suri has been the chairman of IEEE Denver section, has won over 50 awards during his career including project, program and regulatory management, and has held several executive positions.